How Early Implementations Influence Later Adoptions of Innovation: Social Positioning and Skill Reproduction in the Diffusion of Robotic Surgery - Compagni, Amelia; Mele, Valentina; Ravasi, Davide (Academy of Management Journal, 2015)
We report on a multilevel study investigating the diffusion of robotic surgery in the Italian health care system between 1999 and 2010. A combination of qualitative and quantitative methods allowed us to link organization-level processes associated with the adoption and implementation of the innovation to its diffusion at the population level. Our findings advance the understanding of how early experiences with the implementation of an innovation influence later adoptions, and they draw attention to how the search for social gains drives some peripheral actors to pioneer an innovation and engage in practices of discursive persuasion and skill reproduction that, in turn, constitute them to be “exemplary users.” These practices eventually trigger and support the isomorphic diffusion of the innovation, even in the presence of persistent uncertainty about its technical or economic benefits.